Correction of Metabolic Impairments with "Cryocell-Hemocord" Cord Blood Preparation During Acute Purulent Peritonitis - Goltsev, K. A.; Ovsyannikov, S. Ye.; Kozhina, O. Yu.; Ostankov, M. V.; Goltsev, A. N. (Problems of Cryobiology and Cryomedicine, 2011)
The method of correction of metabolic impairments with "Cryocell-Hemocord" cord blood preparation in experimental model in rats with an acute purulent peritonitis was tested. It has been shown that its application with antibiotics as a combined treatment of this pathology contributed to the correction of impairments of free radical oxidation, lessening of hypoxia rate, improvement of oxygen utilization by the tissues, survived hypoxia, recovery of antioxidant protection systems.